Rancang Bangun Perangkat Komunikasi Adaptif Untuk Pengembangan QoS (Quality of Service) Infrastruktur Internet of Vehicle (IoV) - Nizirwan Anwar; Dewanto Rosian Adhy; Rudi Hermawan; Budi Tjahjono; Muhammad Abdullah Hadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
The communication network is an important and vital component in the implementation of the Internet of Vehicle (IoV). The characteristics of IoV related to mobility, load, coverage area is very complex. The movement of connected nodes, communication load and wide coverage require reliable infrastructure support. Coupled with a high level of Quality of Service (QoS) for Internet of Vehicle (IoV) implementation which has a high risk if a communication system failure occurs. In this research, a system that has adaptive capability has been built in choosing a good connection infrastructure at the point where the unit is connected. Created a system that has the ability to connect to several communication network infrastructure. The system can switch to another provider when there is a connection that decreases its QoS level. The tests carried out resulted in better connection dynamics because there was an infrastructure backup. Although there are still many weaknesses because the distribution of network availability is still problematic. Anticipation of network overload can be anticipated with this system. The test results show that there is an increase in the percentage of lines connected to the new system. There is an increase in the percentage of connectivity around 10% to 20% compared to systems without connection backups.